SEDIMENTATION OF MESOZOIKUM ROCK SAWU ISLAND, EAST NUSA TENGGARA - Jati Widiatama, Angga
Sawu Island located on the southwest of the non-volcanic Banda arc reveals Mesozoic rocks which consist of Gondwana passive margin sequences and the drifting sequence. Research on Mesozoic rocks in Sawu Island has already been carried out, but there are significant differences between authors on describe characteristics of the sedimentary rocks and their age. The aim of study to determine the sedimentation character of Savu Island Mesozoic rocks. Methodology in this study included mapping of Mesozoic rocks in Sawu Island, facies stacking pattern analysis and facies association analysis, supported by provenance analysis for siliciclastic rocks, microfacies analysis for carbonate rocks, radiolaria and calcareous nannofossil paleontology analysis to determine relative age, SEM analysis, and XRD analysis to determine the characteristics of claystone physil mineral, and XRF analysis to determine anorganic geochemistry. Data and analysis show that there are eight formations of Mesozoic rocks in Sawu Island which grouped into three tectonostratigraphic units,; (1) Gondwana synrift called the Gondwana sequence consists of Babulu Formation, Quartz Sandstone Unit, Wailuli Formation, and Oebaat Formation, (2) Post-break up Gondwana or Kolbano sequences consisting of the Nakfunu Formation and Ofu Formation, and (3) the rocks resulting from the collision passive margin of Australia with the Banda active margin preferred as Viqueque sequence consisting of the Bobonaro Formation, and the Viqueque Formation. The Babulu Formation consists of conglomeratic sandstones, sandstone, siltstone, marl, and fragmental limestone. It has a distinctive character rich in mica and carbon, with a conccoidal weathering. Halobia sp. become a biomarker for age Late Triassic. The provenance of sandstone originates from transitional continental deposited with turbidite mechanism in basin plain to submarine fan environment. Quartz sandstone units consist of quartz sandstone, siltstone, conglomerates, and coal, aged as Early Jurassic. Conglomerates deposited in braided fluvial. Coal deposited on marsh, intercalation of siltstone and sandstone with flaser and wavy sedimentary structures indicate tidal flat environments, while proven provenance of quartz sandstones cames from interior cratons, and ichnofosil Skolitos deposited on shoreface. Facies association in quartz sandstone units characterizes trangression conditions in estuarine environments. The Wailuli Formation consists of shale, claystone facies, and basalt. The lower part consists of a layer of bioclastic rich shale (radiolarites). Composition of the claystone dominant by clay mineral in the form of smectite as result of tuffaceous altration from passive margin volcanism during the Gondwana rift. The Wailuli Formation is deposited on offshore environment associated with an upwelling zone, aged as Middle Jurassic (Bajocian-Callovian) based on the presence of Beleza decora (Rust). Basalt with faneric-subopitic texture present as intrusion that penetrated between plates as indicated by continental crust contamination. This igneous rock formed as a result adiabatic decompressional melt on the Gondwana rift. The Oebaat Formation consists of sandstone with shale and chert nodules. Sandstones are pale white to pink, medium-sized sand to fine sand with laminated sedimentary structures parallel to thick layers. The layer have sharp to undulatory boundary, at the base of the sandstone shows scouring. The Oebaat Formation is deposited on an submarine fan when lowstand, on the Late Jurassic to Early Cretaceous before breaking up Gondwana in the Valanginia- Hauterivian. The Nakfunu Formation consists of tufa facies and shale facies. The tufa shows radiolaria shell molds and manganese minerals at the boundary of the layers and rock surfaces. Tufa comes from explosive volcanic activity which is associated with the Gondwana final break up. The tufa layer is thinned up and changes the dominance of the red siliceous shale. The Nakfunu Formation deposited on a basin plain environment.